The SLED project and the dynamics of coronal flux ropes. Issue 6 (15th September 2022) - Malherbe, Jean-Marie; Mein, Pierre; Sayède, Frédéric; Rudawy, Pawel; Phillips, Kenneth; Keenan, Francis; Rybák, Jan
Abstract: Investigations of the dynamics of the hot coronal plasma are crucial for understanding various space weather phenomena and making in-depth analyzes of the global heating of the solar corona. We present here numerical simulations of observations of siphon flows along loops (simple semi-circular flux ropes) to demonstrate the capabilities of the Solar Line Emission Dopplerometer (SLED), a new instrument under construction for imaging spectroscopy. It is based on the Multi-channel Subtractive Double Pass (MSDP) technique, which combines the advantages of filters and slit spectrographs. SLED will observe coronal structures in the forbidden lines of FeX 6374 Å and FeXIV 5303 Å, and will measure Doppler shifts up to 150 km s −1 at high precision (50 m s −1 ) and cadence (1 Hz). It is optimized for studies of the dynamics of fast evolving events such as flares or Coronal Mass Ejections (CMEs), as well as for the detection of high-frequency waves. Observations will be performed with the coronagraph at Lomnický Štít Observatory (LSO), and will also occur during total solar eclipses as SLED is a portable instrument.